4k-6=-2k-6-2

Simple and best practice solution for 4k-6=-2k-6-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4k-6=-2k-6-2 equation:


Simplifying
4k + -6 = -2k + -6 + -2

Reorder the terms:
-6 + 4k = -2k + -6 + -2

Reorder the terms:
-6 + 4k = -6 + -2 + -2k

Combine like terms: -6 + -2 = -8
-6 + 4k = -8 + -2k

Solving
-6 + 4k = -8 + -2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2k' to each side of the equation.
-6 + 4k + 2k = -8 + -2k + 2k

Combine like terms: 4k + 2k = 6k
-6 + 6k = -8 + -2k + 2k

Combine like terms: -2k + 2k = 0
-6 + 6k = -8 + 0
-6 + 6k = -8

Add '6' to each side of the equation.
-6 + 6 + 6k = -8 + 6

Combine like terms: -6 + 6 = 0
0 + 6k = -8 + 6
6k = -8 + 6

Combine like terms: -8 + 6 = -2
6k = -2

Divide each side by '6'.
k = -0.3333333333

Simplifying
k = -0.3333333333

See similar equations:

| Y=arcsin(2x+5) | | -10=9(x-9) | | (m*3)+(b*2)+8=45 | | 6(x-20)=36-10x | | 13x-2(x+40)=8x+1 | | 4+x^2-15-6x=0 | | x^2+4=3(2x+5) | | 6x+6y=348 | | x-0.20=56 | | 5x-15=5x-15 | | 111=-3(5+6x) | | .25x+x=3800 | | 87=3(-3x+8) | | 4x(x+4)=9 | | 3n+5-4n=-22 | | 6x-21=33+10x | | 30x+65y=5840 | | -2(7k+9)=25 | | =95-2 | | 2(3x-10)=1 | | 4x+12x=-2254 | | -8(3+9a)=-20 | | 6(3x-10)=46 | | 5(3x-10)=46 | | 4(3x-10)=46 | | 3(3x-10)=46 | | 1(3x-10)=46 | | 12x-25=-63+7x | | 3(-2x+5)=12-4x | | -8x+4=-2(4x-2) | | -y=12-6x | | -20=2y-4 |

Equations solver categories